2008
DOI: 10.1016/j.envres.2008.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Fishing, fish consumption, and awareness about warnings in a university community in central New Jersey in 2007, and comparisons with 2004

Abstract: Fish are a healthy source of protein, but the risks from consuming fish have become a national concern. Over the past 7 years, there have been a number of national advisories regarding saltwater fish. Fish consumption patterns and public knowledge about advisories and warnings have been examined for at-risk populations, but there is little information about the latter for a general population, or of temporal trends in such information acquisition. Information about the benefits and health risks of consuming fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
0
15
0
8
Order By: Relevance
“…According to Burger (2008), the nutritional value of fish and the dissemination of research associating it with health improvements have increased the interest in this food. In his study conducted aiming to obtain data on consumption and awareness about fish, the author found that over 90% of the interviewees had heard about its benefits.…”
Section: Introductionmentioning
confidence: 99%
“…According to Burger (2008), the nutritional value of fish and the dissemination of research associating it with health improvements have increased the interest in this food. In his study conducted aiming to obtain data on consumption and awareness about fish, the author found that over 90% of the interviewees had heard about its benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Entre os benefícios, foram identificados declínios dos níveis de colesterol, da incidência de acidente vascular cerebral, de doença cardíaca, e, possivelmente o risco de Alzheimer. Este alimento pode aumentar a função cognitiva em adultos e impedir o nascimento de crianças com baixo peso e o parto pré-termo [3] .…”
Section: Introductionunclassified
“…The questionnaire was developed based on the literature available that shows obstacles for fish consumption (OETTERER, 2002;TRONDSEN et al, 2003;ZHOU, 2004;HONKANEN;VERPLANKEN, 2005;VERBEKE;VACKIER, 2005;WEI, ZENG, 2005;OLSEN, 2007;BURGER, 2008;SONODA, 2007;MACIEL et al, 2009). These points were clustered, and the items in the tool according to a five-point Likert scale ranging from zero (1) to extreme (5) referring to the fish attributes and characteristics of importance for fish consumption.…”
Section: Sampling and Interview Structurementioning
confidence: 99%
“…Fish consumption can improve cognitive function in adults and prevent the birth of underweight infants as well as preterm delivery birth (BURGER, 2008).…”
Section: Introductionmentioning
confidence: 99%